New Directions in Geometric and Applied Knot Theory - Blatt, Simon; Reiter, Philipp; Schikorra, Armin (De Gruyter Open Poland, 2018)
The aim of this book is to present recent results in both theoretical and applied knot theory-which are at the same time stimulating for leading researchers in the αeld as well as accessible to non-experts. The book comprises recent research results while covering a wide range of di erent sub-disciplines, such as the young αeld of geometric knot theory, combinatorial knot theory, as well as applications in microbiology and theoretical physics.